Impact of overwork on self-assessed health of rural-to-urban migrants: Limitations of work incentives moderation effect and industry heterogeneity - Zhaoxin Huo; Ya Wang (PLoS ONE, 2025)
Overwork is widely recognized as harmful to workers’ physical and mental health, yet studies focusing on income-driven rural-to-urban migrants are lacking. This research aims to explore the effects of working hours on the health of rural-to-urban migrants in China, examining the moderating role of work incentives and industry heterogeneity. Using 2018 China Labor-force Dynamics Survey (CLDS) data, we analyzed 3,475 valid samples with a binary logit model, categorizing working hours into comfortable work, tolerable work, moderate overwork, and severe overwork. Interaction and subgroup regression models were employed to examine the moderating effects of work incentives across industries. The results indicate that comfortable work does not improve health, while moderate overwork is harmful, with severe overwork having a greater negative impact. This effect is stronger for rural-to-urban migrants in capital-intensive industries compared to labor-intensive industries. Work incentives only mitigate health damage from overwork in labor-intensive sectors, but this effect disappears under severe overwork across all industries. This study contributes by highlighting the unique health impacts of overwork on income-driven rural-to-urban migrants and revealing the limitations of work incentives and industry differences, offering new insights into the relationship between employment and health.